Finding competitive intelligence on Internet start-up companies: a study of secondary resource use and information-seeking processes (Information Research: An International Electronic Journal)
The paper reports findings from a study of CI activities involving Internet start-up companies in the telecommunications industry. The CI gathering was conducted by graduate students in library and information science in the context of a class project for a real business client, itself a small Internet start-up company. The primary objective of the study was to provide empirical insights into the applicability of specific types of secondary information resources to finding competitive intelligence information on small Internet start-up companies. An additional objective was to identify the characteristics of research strategies applied in the collection of CI on Internet start-ups from the perspective of current conceptual frameworks of information-seeking behaviour presented in the library and information science literature. This study revealed some interesting findings regarding the types of secondary information resources that can be used to find competitive intelligence on small, Internet start-up companies. The study also provided insight into the characteristics of the overall information-seeking strategies that are applied in this type of competitive intelligence research.